Value of Quantitative and Qualitative Analyses of Circulating Cell-Free DNA as Diagnostic Tools for Hepatocellular Carcinoma: A Meta-Analysis - Liao, Wenjun (Medicine (Baltimore), 2015)
Qualitative and quantitative analyses of circulating cell-free DNA (cfDNA) are potential methods for the detection of hepatocellular carcinoma (HCC). Many studies have evaluated these approaches, but the results have been variable. This meta-analysis is the first to synthesize these published results and evaluate the use of circulating cfDNA values for HCC diagnosis. All articles that met our inclusion criteria were assessed using QUADAS guidelines after the literature research. We also investigated 3 subgroups in this meta-analysis: qualitative analysis of abnormal concentrations of circulating cfDNA; qualitative analysis of single-gene methylation alterations; and multiple analyses combined with alpha-fetoprotein (AFP). Statistical analyses were performed using the software Stata 12.0. We synthesized these published results and calculated accuracy measures (pooled sensitivity and specificity, positive/negative likelihood ratios [PLRs/NLRs], diagnostic odds ratios [DORs], and corresponding 95% confidence intervals [95% CIs]). Data were pooled using bivariate generalized linear mixed model. Furthermore, summary receiver operating characteristic curves and area under the curve (AUC) were used to summarize overall test performance. Heterogeneity and publication bias were also examined. A total of 2424 subjects included 1280 HCC patients in 22 studies were recruited in this meta-analysis. Pooled sensitivity and specificity, PLR, NLR, DOR, AUC, and CIs of quantitative analysis were 0.741 (95% CI: 0.610–0.840), 0.851 (95% CI: 0.718–0.927), 4.970 (95% CI: 2.694–9.169), 0.304 (95% CI: 0.205–0.451), 16.347 (95% CI: 8.250–32.388), and 0.86 (95% CI: 0.83–0.89), respectively. For qualitative analysis, the values were 0.538 (95% CI: 0.401–0.669), 0.944 (95% CI: 0.889–0.972), 9.545 (95% CI: 5.298–17.196), 0.490 (95% CI: 0.372–0.646), 19.491 (95% CI: 10.458–36.329), and 0.87 (95% CI: 0.84–0.90), respectively. After combining with AFP assay, the values were 0.818 (95% CI: 0.676–0.906), 0.960 (95% CI: 0.873–0.988), 20.195 (95% CI: 5.973–68.282), 0.190 (95% CI: 0.100–0.359), 106.270 (95% CI: 22.317–506.055), and 0.96 (95% CI: 0.94–0.97), respectively. The results in this meta-analysis suggest that circulating cfDNA have potential value for HCC diagnosis. However, it would not be recommended for using independently, which is based on the nonrobust results. After combining with AFP, the diagnostic performance will be improved. Further investigation with more data is needed.